A new 3D printing-based approach to understand drug release mechanisms from amorphous solid dispersion tablets - Awaji, Safhi (2020)
Amorphous solid dispersions (ASDs) can be a successful approach to improve the apparent solubility and hence the bioavailability of poorly water-soluble drugs, specifically BCS class II ingredients. However, it has been reported that an increase in active pharmaceutical ingredient (API) loading can lead to a decrease in the API release rate from the formulation, due to recrystallisation in vitro/vivo, often driven by crystalline seeds in random locations in formulation. Up to now, it has been difficult to fabricate ASD tablets with controlled distribution of crystalline seeds in various positions of the formulation to study the release of APIs, because conventional tabletting methods do not easily aﬀord precise spatial control of these impurities during tablet manufacturing. Consequently, fabrication of such solid dosage forms spiked with crystalline impurities may be possible by employing three-dimensional (3D) printing technologies due to their ability to control numerous parameters during the printing process. Therefore, we aim to investigate the dissolution behaviour of the API from ASD tablets by fabricating two basic ASD model tablets (pure ASD and spiked) by employing one of the 3D printing techniques in which the effect of spatial location of crystal seeds can be systematically controlled and evaluated to understand drug release mechanisms from such type of dosage forms and offer recommendations. The present thesis investigates the dissolution behaviour of two basic ASD model tablets i.e. pure ASD and amorphous tablets spiked with crystalline seeds, which is a tablet manufactured as compartment with an outer shell (amorphous or spiked) and an inner core (amorphous or spiked), fabricated utilising fused deposition modelling (FDM) 3D printing technique. A well-documented low water-soluble drug i.e., felodipine (FELD) was selected once and used as a model drug throughout the present thesis. Also, polyvinyl alcohol (PVA), which is one of the most commonly used thermoplastic polymers with the FDM 3D printer, was selected as the main polymer with which to fabricate the two basic ASD formulations. The steps that were taken towards fabricating the model tablets were detailed in chapter 3, 4, and 5. Starting in chapter 3 by predicting the miscibility of FELD with two polymers, namely PVA, and Soluplus®, utilising the Flory-Huggins theory and the melting point depression approach (dissolution endpoint) to select the drug loadings which then used to manufacture the printer feedstocks utilising hot melt extruder (HME). For the FELD-PVA system the miscibility was calculated for the first time in the present work. The FELD has shown complete miscibility with both polymers, PVA and Soluplus®, for all the drug-polymer compositions (5%- 75%) at temperatures above 140°C. In contrast, The FELD was predicted to be miscible with both polymers for drug loadings lower than 10% (w/w) at room temperature. Moreover, the composition phase diagrams for both systems, FELD-PVA and FELD-Soluplus®, were successfully constructed. Accordingly, different drug loadings, including 10% (metastable zone), and 50% (unstable zone), were selected for the formulation of the FDM 3D printer feedstocks and model tablets in chapter 4. In chapter 4, the selected drug loadings were successfully used to manufacture the FDM 3D printer feedstocks utilising HME. It was possible to fabricate the pure ASD model tablets with different geometries utilising the FDM 3D printer due to the high temperature (above 160°C) used during both process, the formulation of the printer feedstocks using HME and fabrication of the model tablets utilising the FDM 3D printer. In contrast, it was challenging to manufacture spiked model tablets with controlled spatial distribution of crystalline seeds during the model tablets fabrication process. Thus, relative humidity (RH) storage conditions were used as an approach to achieve equilibrium (crystallinity) in the manufactured materials in order to fabricate the spiked model tablets. In chapter 5, we successfully manufactured the FDM 3D printer drug loaded feedstock utilising HME. Then, the manufactured printer feedstock was used to fabricate different compartment model tablets i.e., fresh shell- fresh core (control), fresh shell- aged core, aged shell- fresh core, and aged shell- aged core (control), utilising the FDM 3D printer and 75% humidity. The crystallinity % of the FELD in the spiked models, fresh shell-aged core, aged shell- fresh core, and aged shell- aged core, was quantified using DSC and found to be about 6%. The spiked model tablets were fabricated for the first time in the present work. The dissolution performance of the different model tablets was investigated utilising USP dissolution apparatus I (basket). The FELD release from the fabricated formulations has shown a sustained release (SR) for a period of 10 hours in two pH media, pH 2 and pH 6.8. In both media, the observed dissolution of the FELD from the fabricated model tablets was ranked as fresh shell-fresh core > fresh shell-aged core > aged shell-fresh core > aged shell-aged core. The obtained dissolution profiles from the utilised spiked formulations suggested that the model tablets fabricated with a fresh shell-aged core have shown drug release close to that obtained from the model tablets fabricated as a pure amorphous tablet. Accordingly, this result suggests that the fresh outer shell of the fabricated model tablets may have dissolved, and the release was predominantly controlled by the outer shell rather than the spiked inner core. In contrast, the obtained dissolution of the aged shell-fresh core model tablets has shown FELD drug release close to that obtained for the control fabricated as aged shell-aged core model tablets, which suggests that the drug release was predominantly controlled by the spiked outer shell rather than the fresh inner core due to the induced crystallinity in the outer shell with time. The FDM 3D printing technique is promising as a fabrication process to build better ASD test model tablets with controlled spatial distribution and amount of crystalline seeds than the conventional tabletting method in order to investigate why ASD tablets fail dissolution testing. Following this work, the FDM 3D printing technique can be considered for future development of ASD tablets in the industry to build model tablets with defined amount and location of crystalline seeds to understand the dissolution behaviour from these formulations.